Encouraging pro-environmental behaviours: A review of methods and approaches - Gianluca Grilli; John A. Curtis (The Economic and Social Research Institute (ESRI), 2019)
Many urgent environmental problems can be mitigated with more sustainable use of resource. An acknowledgement of which is a growing interest among policy practitioners in encouraging pro-environmental behaviour change initiatives. The effect of anthropic pressure on the environment is long known and the first pro-environmental behaviour studies date back to the middle 1970s. Despite this, the scientific literature has not yet answered several questions: what are the most suitable ways to encourage behavioural changes? What are the barriers to project implementation? What are the long run effects of behavioural change projects? With this in mind, this contribution offers a review of the existing literature on behavioural change case studies and provides a categorisation of treatments and guidelines for successful project implementation. Five different approaches have been considered: education and awareness, social influence, relationship building, incentives and nudges, which have been used in experimental studies. On balance the case studies suggest that all approaches are suitable but their selection should be based on specific objectives and target population. Interestingly, the choice of the behaviour to change is rarely discussed before project implementation. This analysis also highlights that little is known on whether behaviour change projects achieve sustained pro-environmental behavioural change over time.
Keywords: 330